CHOICE OF LISINOPRIL FOR TREATMENT OF HYPERTENSION IN PATIENTS WITH CONCOMITANT DISEASES - N. A. Dzhaiani (Рациональная фармакотерапия в кардиологии, 2015)
Rationale and benefits of the use of the ACE inhibitor lisinopril in the clinical practice as an antihypertensive drug are considered. Special attention is paid to the organ protective effects of lisinopril and its application in some clinical situations (combination of hypertension with chronic obstructive pulmonary disease, elderly patients, and concomitant liver diseases).